Workplace Stressors and Work Engagement Among Married Nurses: The Roles of Psychological Distress and Perceived Partner Responsiveness - Hu Ying; Jie Liu; Xiaofu Pan (Healthcare, 2026)
Background/Objectives: Understanding threats to nurses’ work engagement is important for workforce stability, care quality, and nurses’ well-being. We examined whether organizational dehumanization and patient/family incivility were indirectly associated with lower work engagement through psychological distress and whether perceived partner responsiveness moderated the distress–engagement association. Methods: Three-wave survey data were collected from 325 married nurses at one-week intervals. Workplace stressors were measured at Time 1, psychological distress and perceived partner responsiveness at Time 2, and work engagement at Time 3. Covariate-adjusted moderated mediation analyses were conducted using 5000 bootstrap samples. Results: Organizational dehumanization (β = 0.438, p < 0.001) and patient/family incivility (β = 0.271, p < 0.001) were independently associated with greater psychological distress, which was associated with lower work engagement (β = −0.246, p < 0.001). The psychological distress × perceived partner responsiveness interaction was significant (β = 0.305, p < 0.001), explaining an additional 6.3% of the variance in work engagement. The negative distress–engagement association was significant at low and mean levels of perceived partner responsiveness but not at a high level. Both workplace stressors showed significant indirect associations with work engagement at low and mean, but not high, levels of perceived partner responsiveness; the corresponding high–low contrasts were significant. Conclusions: The findings are consistent with a pattern in which workplace stressors from different sources are associated with lower work engagement through psychological distress, while higher perceived partner responsiveness is associated with a weaker distress–engagement relationship. Reducing avoidable workplace stressors and supporting recovery outside work may help sustain nurses’ engagement; causal and intervention effects remain to be tested.